Enhancing motor skills and physical activity in students with ADHD through an inclusive physical literacy model using video modeling - Darmawan, Arief; Fitriady, Gema; Sari, Zihan Novita; Priyohutomo, Ahadi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Children with attention deficit hyperactivity disorder (ADHD) often experience delays in motor development and exhibit unstructured physical activity, which may hinder the acquisition of controlled motor skills. These limitations can negatively affect their overall physical health and quality of life. Although inclusive physical education has shown promise, limited research explores the impact of structured video modeling on this population. Research Objective: This study aimed to examine the effectiveness of an inclusive physical literacy model based on video modeling in improving motor skills and physical activity among students with ADHD. Method: An experimental design with a randomized control group pretest-posttest approach was used. The participants were 20 inclusive students diagnosed with ADHD. Motor skills were assessed using selected subtests from the test of gross motor development (TGMD), including horizontal jumping, hopping, and sprinting. Physical activity levels were measured using the physical activity questionnaire for children (PAQ-C). Finding/Results: Independent t-test analysis revealed a significant improvement in the intervention group compared to the control group. The posttest results showed significant differences in motor skills (p = 0.046) and physical activity levels (p = 0.001). Conclusion: The findings indicate that an inclusive physical literacy model incorporating video modeling can effectively enhance both motor skills and physical activity in students with ADHD. This approach supports not only physical development but also fosters better psychological and social outcomes. Future studies are encouraged to implement this model on a larger and more diverse scale.